2017
DOI: 10.1007/s12031-017-0880-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Sequencing Reveals MicroRNAs Downregulated in Cerebral Cavernous Malformations

Abstract: Cerebral cavernous malformations (CCM) are vascular lesions associated with loss-of-function mutations in one of the three genes encoding KRIT1 (CCM1), CCM2, and PDCD10. Recent understanding of the molecular mechanisms that lead to CCM development is limited. The role of microRNAs (miRNAs) has been demonstrated in vascular pathologies resulting in loss of tight junction proteins, increased vascular permeability and endothelial cell dysfunction. Since the relevance of miRNAs in CCM pathophysiology has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Circulating miRNome have been a major interest to the research community during recent decades and rigorous scientific effort have led major medical breakthroughs in the oligonucleotide research field [31]. To our knowledge, only one study has sequenced the intra-lesional miRNome of resected human CCM lesions [25]. Our group has also previously identified circulating miRNAs in human patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNome have been a major interest to the research community during recent decades and rigorous scientific effort have led major medical breakthroughs in the oligonucleotide research field [31]. To our knowledge, only one study has sequenced the intra-lesional miRNome of resected human CCM lesions [25]. Our group has also previously identified circulating miRNAs in human patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins already implicated in CCM lesions were found to be targets of these miRNAs including MLLT4, VEGFA, MAPK1, RAC1, RHOA, FOXO1, ENG, SMURF1, and HEYL [17,83,99,106,126,139] . It was concluded that three miRNAs (let-7b-5p, miR-361-5p, and miR-370-3p) can potentially be involved in the pathogenesis of CCM [172] .…”
Section: Cellular Functions and Biogenesismentioning
confidence: 99%
“… 15 miR-361-5p has been identified as one of the top five cerebral cavernous malformations-relevant miRNAs. 16 miRNAs are well known to induce translational repression by binding to their complementary target mRNAs. 17 The present study identified cathepsin B ( CTSB ) as a target of miR-361 .…”
Section: Introductionmentioning
confidence: 99%